A Realtime Record Data Berbasis Desktop Pada Monitoring Penyimpanan Kentang - Agung Kridoyono; Mochamad Sidqon (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2019)
In many condition of potatoes storage made extra observation. Potatoes condition like defect, placement, dan typical storage had effect on potatoes durability. This instrument to help observation of potatoes when places on storage, with real time record model made the changes condition of potatoes can be observed anytime. Serial asyncronous communication mode made data transfer between microcontroller with personal computer where the data storage had been saved on PC database. This model hopefully help farmer to observe potatoes condition on climate changes. The ideal condition of potatoes is 40C for temperature and 75-90% RH for humidity. So we have set point on stability of media. The result of research had two system model like environment and data storage with interface that built by Delphi desktop programming Keywords: waterproff sensor, water shield teqnique, microkontroller monitoring